Exploration of Students' Perceptions of Augmented Reality (AR)-Based Islamic Education Learning in Grade IX of SMPN 1 Montong - Ima Seftiyana Safira (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to explore students' perceptions of Augmented Reality (AR)-based Islamic Religious Education (PAI) learning in ninth grade at SMPN 1 Montong. The use of AR in learning is seen as a 21st-century educational innovation capable of improving conceptual understanding, motivation, and active student engagement. This study used a qualitative approach with descriptive analytical methods through interviews, observations, and questionnaires. The results showed that the majority of students had positive perceptions of AR use because the technology provides concrete and interactive visualizations, facilitating the understanding of abstract material. Learning becomes more engaging, collaborative, and encourages active student participation. Factors influencing student perceptions include the ease of use of the application, the role of teachers in mentoring, the quality of the devices, and the readiness of the learning environment. Obstacles identified were related to technical difficulties for a small number of students. Overall, AR is considered to have significant potential in improving the effectiveness of PAI learning and can be a relevant alternative learning medium in the digital age.